Effectiveness of cognitive behaviour therapy for the treatment of catastrophisation in patients with fibromyalgia: a randomised controlled trial - Alda, Marta (BioMed Central, 2011)
INTRODUCTION: No randomised, controlled trials have been conducted to date on the efficacy of psychological and pharmacological treatments of pain catastrophising (PC) in patients with fibromyalgia. Our aim in this study was to assess the effectiveness of cognitive-behaviour therapy (CBT) and the recommended pharmacological treatment (RPT) compared with treatment as usual (TAU) at the primary care level for the treatment of PC in fibromyalgia patients. METHODS: We conducted a six-month, multicenter, randomized, blinded, parallel group, controlled trial in which patients were randomly assigned to one of three study arms: CBT (n = 57), RPT (n = 56) and TAU at the primary care level (n = 56). The major outcome of this study was PC in patients with fibromyalgia. The secondary variables were pain acceptance, depression, anxiety, pain, global function and quality of life. RESULTS: CBT significantly decreased global PC at the six-month follow-up examination with effect sizes of Cohen's d = 0.73 and 1.01 compared with RPT and TAU, respectively. CBT was also more effective than RPT and TAU at increasing pain acceptance at the six-month follow-up examination (effect sizes of Cohen's d = 0.77 and 0.80, respectively). Compared with RPT and TAU, CBT was more effective at improving global function based on the Fibromyalgia Impact Questionnaire (six-month effect sizes Cohen's d = 0.44 and 0.53, respectively) and quality of life based on the European Quality of Life Scale (six-month effect sizes Cohen's d = 0.11 and 0.40, respectively). There were no differences among the three treatments with regard to pain and depression. CONCLUSIONS: CBT shows higher efficacy than RPT and TAU not only in key outcomes in FM, such as function and quality of life, but also in relevant mediators of treatment effects, such as pain catastrophising and pain acceptance. TRIAL REGISTRATION: ISRCTN: ISRCTN10804772